Antimicrobial use in Canadian acute-care hospitals: Findings from three national point-prevalence surveys between 2002 and 2017. (7th November 2022) - Liang, Jennifer J.; Rudnick, Wallis; Mitchell, Robyn; Brooks, James; Bush, Kathryn; Conly, John; Ellison, Jennifer; Frenette, Charles; Johnston, Lynn; Lavallée, Christian; McGeer, Allison; Mertz, Dominik; et al.
Abstract: Objectives: The Canadian Nosocomial Infection Surveillance Program conducted point-prevalence surveys in acute-care hospitals in 2002, 2009, and 2017 to identify trends in antimicrobial use. Methods: Eligible inpatients were identified from a 24-hour period in February of each survey year. Patients were eligible (1) if they were admitted for ≥48 hours or (2) if they had been admitted to the hospital within a month. Chart reviews were conducted. We calculated the prevalence of antimicrobial use as follows: patients receiving ≥1 antimicrobial during survey period per number of patients surveyed × 100%. Results: In each survey, 28−47 hospitals participated. In 2002, 2, 460 (36.5%; 95% CI, 35.3%−37.6%) of 6, 747 surveyed patients received ≥1 antimicrobial. In 2009, 3, 566 (40.1%, 95% CI, 39.0%−41.1%) of 8, 902 patients received ≥1 antimicrobial. In 2017, 3, 936 (39.6%, 95% CI, 38.7%−40.6%) of 9, 929 patients received ≥1 antimicrobial. Among patients who received ≥1 antimicrobial, penicillin use increased 36.8% between 2002 and 2017, and third-generation cephalosporin use increased from 13.9% to 18.1% ( P < .0001). Between 2002 and 2017, fluoroquinolone use decreased from 25.7% to 16.3% ( P < .0001) and clindamycin use decreased from 25.7% to 16.3% ( P < .0001) among patients who received ≥1 antimicrobial. Aminoglycoside use decreased from 8.8% to 2.4% ( P < .0001) and metronidazole use decreased from 18.1% to 9.4% ( P < .0001). Carbapenem use increased from 3.9% in 2002 to 6.1% in 2009 ( P < .0001) and increased by 4.8% between 2009 and 2017 ( P = .60). Conclusions: The prevalence of antimicrobial use increased between 2002 and 2009 and then stabilized between 2009 and 2017. These data provide important information for antimicrobial stewardship programs.